Capacity strengthening strategy through capacity needs assessment for Country Level Strategic Analysis and Knowledge Support System (SAKSS): Mozambique - Zandamela, Carlos (International Food Policy Research Institute, 2014)
This study was undertaken for the Regional Strategic Analysis and Knowledge Support System of Southern Africa (ReSAKSS‐SA) with the purpose of identifying country‐specific needs for strategic agricultural policy analysis, investment planning and implementation, monitoring and evaluation (M&E), and knowledge management. It also aimed to identify the capacities needed in the short, medium, and long term to strengthen SAKSS in Mozambique. Mozambique’s agricultural sector is the major source of income and the base for food security for the majority of the population. However, food insecurity and chronic malnutrition are still Mozambique’s major challenges. The government of Mozambique, in collaboration with partners, has been engaged in designing and implementing policies, strategies, programs, and projects aimed at improving the agriculture sector’s performance.